VV-ECMO combined with prone position ventilation in the treatment of Pneumocystis jirovecii pneumonia: A case report. Issue 1 (7th January 2022) - Jia, Lijing; Zhang, Zhiyang; Bai, Yinxiang; Du, Quansheng
Abstract: Introduction: Pneumocystis jirovecii pneumonia (PJP) occurs in immunocompromised hosts. It is classified as PJP with human immunodeficiency virus (HIV) infection (HIV-PJP) and PJP without HIV infection (non-HIV PJP). Compared with HIV-PJP, non-HIV PJP is more likely to develop rapidly into respiratory failure, with difficult diagnosis and high mortality. Patient concerns: A 46-year-old male with membranous nephropathy was treated with oral corticosteroids and tacrolimus. He was admitted to our hospital for fever and dyspnea which developed 4 days ago. Laboratory data revealed that leukocytes were 10.99 × 10 9 /L, neutrophils 87.7%, lymphocytes 9.6%, C-reactive protein 252.92 mg/L, New coronavirus nucleic acid detection negative. CT scan of chest revealed ground-glass opacity in both lungs. He was admitted to the respiratory department of our hospital, and then transferred to ICU because of his critical condition. Diagnosis: High throughput gene detection of pathogenic microorganisms in alveolar lavage fluid showed that the detection sequence of Pneumocystis yersiniae increased significantly. The serum HIV-antibody was negative. Therefore, the patient was diagnosed as non-HIV PJP. Interventions: After admission, the patient was assisted by noninvasive ventilator and treated with compound trimethoprim-sulfamethoxazole (SMX-TMP) and caspofungin. The patient's condition continued to deteriorate, and then underwent endotracheal intubation and veno-venous extracorporeal membrane oxygenation (VV-ECMO) combined with prone position ventilation until the lung lesion improved. Outcomes: VV-ECMO was stopped on day 12, tracheal intubation was removed after 2 days. The patient was transferred to the respiratory department on day 15, discharged after 12 days without complications. Two months later, the follow-up showed that the patient was in good condition. Conclusion: VV-ECMO combined with prone position ventilation could be a useful choice for respiratory assistance in non-HIV PJP patients.